Rights and Wrong(s): Theorizing Judicial Decisions as Normative Choices - Cherry, Keith (Université d'Ottawa / University of Ottawa, 2012)
This thesis contends certain contentious court cases can be traced beyond their legal roots to deep, sometimes incommensurable philosophical disagreements. However, the unitary nature of the judicial system effectively forces the court to take sides, putting its institutional weight and moral authority behind one set of principles and not another. Following Cover, I contend that this encourages future litigants to rephrase their claims in the court’s preferred normative language, thus influencing our normative environment. The theories which guide judicial decisions, however, are generally insufficiently attentive to the court’s normative influence. In response, I attempt adapting Dworkin’s Law as Integrity around Cover’s more sociological view. Chapter 1 examines Cover’s view, Chapter 2 explores Syndicat Northcrest v. Amselem and Delmaagukw v. B.C. as case studies, and Chapter 3 adapts Dworkin around Covers view. My conclusions argue that further inspiration can be drawn from EU Coordinate Constitutionalism and Sui Generis aboriginal rights.
Keywords: Law; Legal Philosophy; Dworkin; Cover; Jurisgenerative; Syndicat Northcrest v. Amselem; Delmaagukw v. B.C.; oral history; narrative; Legal Pluralism; multiculturalism; religious freedom; Law as Integrity